Between Devolution and Direct Rule: Implications of a Political Vacuum in Northern Ireland?. Issue 2 (2nd May 2018) - Heenan, Deirdre; Birrell, Derek
Abstract: It is over a year since the collapse of the devolved administration at Stormont, which left one region of the United Kingdom without a functioning executive. Reluctance to introduce direct rule from Westminster reduced Northern Ireland to a desiccated form of governance. This article examines the nature and form of government in this political vacuum. The consequences of this system are examined in terms of the absence of legislation, mechanisms for scrutiny, and participation in intergovernmental relations. In the absence of devolution and direct rule, the potential for greater involvement of the Irish government in the affairs of Northern Ireland is also considered.